PENINGKATAN KEMAMPUAN DISPOSISI MATEMATIS SISWA SMP DENGAN MODEL PEMBELAJARAN ASSURE - Sumliyah Sumliyah; Indriyani Indriyani; Rifqi Hidayat (Program Studi Pendidikan Matematika, FKIP Universitas Muhammadiyah Cirebon, 2017)
The research is based on the law of mathematical disposition and the less of the students’sactivation in learning process. The research objective is to know the improvement of mathematicaldisposition which the learning process used is ASSURE learning model with conventional learning.The research is Quasi Experimental research.The research design is used Nonequivalent ControlGroup Design and sample collection technique is Sampling Purposive .The population in theresearch is the students of class 8th SMPN 1 Sumber Kabupaten Cirebon, academic year2017/2018. The sample of the research is the 8th qraders 36 th student class 8th D is classeseksperimental and 38 th student class 8th F is classes control. Based on the result of the difference ofthe average of post-test using the test of Independent Sample T-Test equals sig (2 tailed) score0,000 < 0,05 means H0 rejected. And then the difference of the average using of N-gain using thetest of Independent Sample t-test equals sig score (1 tiled) 0,0005 < 0,05 means H0 rejected. On theother hard, based on the result of questionnaire using the test of Mann Whitney U-Test egualsAsymp. Sig(2 tailed) 0,000 < 0,5 means H0 rejected. The research result shows that: Theimprovement of mathematical disposition which is using ASSURE learning model is better thanthe students who are learning by conventional learning process.Key Words: ASSURE, Mathematical Disposition.